FBXO45-MYCBP2 regulates mitotic cell fate by targeting FBXW7 for degradation - Richter, Kai; Kschonsak, Yvonne T.; Vodicska, Barbara; Hoffmann, Ingrid (Cell death and differentiation, 2020)
Cell fate decision upon prolonged mitotic arrest induced by microtubule-targeting agents depends on the activity of the tumor suppressor and F-box protein FBXW7. FBXW7 promotes mitotic cell death and prevents premature escape from mitosis through mitotic slippage. Mitotic slippage is a process that can cause chemoresistance and tumor relapse. Therefore, understanding the mechanisms that regulate the balance between mitotic cell death and mitotic slippage is an important task. Here we report that FBXW7 protein levels markedly decline during extended mitotic arrest.